2015
DOI: 10.1039/c4nj01995d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen production under a visible light source and dye degradation under natural sunlight using nanostructured doped zinc orthotitanates

Abstract: Nanostructured zinc orthotitanates were successfully employed as solar light driven photocatalysts for waste degradation such as H2S which produces H2, a clean energy source, and dye degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…The samples ZT‐150 (500), ZT‐180 (500) and ZT‐200 (500) show two band gaps; first in the range 3.3 eV to 3.5 eV and the second around 3.2 eV. The first band gap (3.3 eV to 3.5 eV) is attributed to the presence of cubic Zn 2 TiO 4 and the second band gap around 3.2 eV is attributed to the presence of tetragonal Zn 2 TiO 4 ,. Nikam et al have reported two band gaps in Zn 2 TiO 4 ; first one around 3.7 eV attributed to the presence of cubic Zn 2 TiO 4 and the second one at about 3.22 eV due to tetragonal Zn 2 TiO 4 .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The samples ZT‐150 (500), ZT‐180 (500) and ZT‐200 (500) show two band gaps; first in the range 3.3 eV to 3.5 eV and the second around 3.2 eV. The first band gap (3.3 eV to 3.5 eV) is attributed to the presence of cubic Zn 2 TiO 4 and the second band gap around 3.2 eV is attributed to the presence of tetragonal Zn 2 TiO 4 ,. Nikam et al have reported two band gaps in Zn 2 TiO 4 ; first one around 3.7 eV attributed to the presence of cubic Zn 2 TiO 4 and the second one at about 3.22 eV due to tetragonal Zn 2 TiO 4 .…”
Section: Resultsmentioning
confidence: 98%
“…The first band gap (3.3 eV to 3.5 eV) is attributed to the presence of cubic Zn 2 TiO 4 and the second band gap around 3.2 eV is attributed to the presence of tetragonal Zn 2 TiO 4 ,. Nikam et al have reported two band gaps in Zn 2 TiO 4 ; first one around 3.7 eV attributed to the presence of cubic Zn 2 TiO 4 and the second one at about 3.22 eV due to tetragonal Zn 2 TiO 4 . The band gap values for bulk cubic ZnTiO 3 and bulk cubic Zn 2 TiO 4 are 3.8 and 3.7 eV, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations